Effect of flavonoids on neurodegenerative diseases caused by acrylamide: Based on the perspective of intestinal flora - Xing Ge; Yidan Cai; Haochen Dai; Yuhan Jiang; Songmei Luo; Xin Zhang; Yuchen Zhu (Journal of Future Foods)
ABSTRACT: Acrylamide (AA) is a typical by-product of the Maillard reaction in food processing. AA can destroy the antioxidant balance, induce neurotoxicity, and affect the occurrence and development of neurodegenerative diseases. Disturbances in the gut microbiota can lead to neurological diseases. Flavonoids have multiple biological activities, such as antioxidant, anti-inflammatory, and regulation of intestinal flora structure, and have a certain intervention effect on the neurotoxicity of AA. The gut microbiota has a variety of mechanisms affecting brain homeostasis and neurodevelopment, and regulating the gut microbiota can effectively improve the severity of neurodegenerative diseases. This article calls for attention to the role of flavonoids in the AA-mediated neurogenic disease prevention and control pathway and proposes a positive effect between plant-based diet and brain health.